Assessing the effect of rbST on mammary gland growth and reproductive characteristics Holstein × Gyr pre-pubertal heifers; Modelling the impact of mastitis on milk yield losses - Sguizzato, Anna Luiza Lacerda (2023)
In this thesis, two chapters were based on a study with Holstein × Gyr pre-pubertal heifers and one on modeling mastitis data. The objective of the first chapter was to evaluate the effects of recombinant bovine somatotropin (rbST) on digestibility, performance, blood metabolites, mammary gland development, and carcass composition of high-performance pre-pubertal Holstein × Gyr heifers. It was observed that the rbST did not influence digestibility or performance parameters, increased IGF1 concentration and ribeye area, reduced parenchyma and fat pad pixels/mm², and decreased IGFBP3 expression in the mammary gland. In summary, rbST injections can be used to overcome the detrimental effects of high-performance diets on mammary gland growth and to improve lean carcass gain of pre-pubertal Holstein × Gyr heifers. For the second chapter, the objective was to assess the effects of rbST on reproductive traits, steroid concentration, and gene expression of cumulus-oocyte complex of high-performance pre-pubertal Holstein × Gyr heifers (same heifers and protocols mentioned in the first chapter). As expected, some heifers achieved puberty during the trial, approximately 36% of the assessed females. However, neither puberty attainment nor age, weight, or height at puberty were influenced by treatment. The reproductive condition did not affect ovary size, but there was an interaction effect of treatment and day, where heifers from the rbST treatment had greater ovary size on days 36, 43, 50, and 57. The rbST pubertal heifers had greater follicle sizes compared to the no rbST females on days 15 and 57, but no rbST heifers had larger follicles on days 71 and 85. Gene expression assessment resulted in a greater mRNA abundance of IGF1R on the cumulus-oocyte complex of heifers on no rbST treatment. To conclude, the evidence gathered in this study supports the hypothesis that the use of rbST would impact on reproductive characteristics of Holstein × Gyr heifers. The objective of the third chapter was to describe the impact of mastitis on milk production based on mastitis degree and moment of occurrence. Data from thirteen dairy farms were collected, generating a databank of 908,816 daily individual milk test records from 3,508 cows in different lactations, from January 2017 to December 2022. Mastitis drop and recovery were modeled following three steps: removal of milk recorded at the diagnosis day of mastitis from the databank and fit of a Wood’s Curve for each cow and lactation order; return of mastitis data to the database and estimation of the residual milk loss due to mastitis from 6 days before and after the mastitis event; use of a meta-analytical approach, including farm as a random control effect, to estimate residual milk loss. The estimations suggest that milk drop occurs three to four days prior to mastitis onset and can last until ten to twelve days from the diagnosis. Moreover, milk losses are greater than the values referenced in the literature and differ due to mastitis level. The novelty of our study indicates when and to what proportion mastitis drop and recovery occur and brings new perspectives to mastitis modeling. Keywords: Crossbred. Somatotropin. IGFBP3. Reproduction. Modelling. Milk production. Mastitis.